Cost‐effectiveness of rapid hepatitis C virus (HCV) testing and simultaneous rapid HCV and HIV testing in substance abuse treatment programs. (January 2015) - Schackman, Bruce R.; Leff, Jared A.; Barter, Devra M.; DiLorenzo, Madeline A.; Feaster, Daniel J.; Metsch, Lisa R.; Freedberg, Kenneth A.; Linas, Benjamin P.
Abstract Aims To evaluate the cost‐effectiveness of rapid hepatitis C virus (HCV) and simultaneous HCV/HIV antibody testing in substance abuse treatment programs. Design We used a decision analytic model to compare the cost‐effectiveness of no HCV testing referral or offer, off‐site HCV testing referral, on‐site rapid HCV testing offer and on‐site rapid HCV and HIV testing offer. Base case inputs included 11% undetected chronic HCV, 0.4% undetected HIV, 35% HCV co‐infection among HIV‐infected, 53% linked to HCV care after testing antibody‐positive and 67% linked to HIV care. Disease outcomes were estimated from established computer simulation models of HCV [Hepatitis C Cost‐Effectiveness (HEP‐CE)] and HIV [Cost‐Effectiveness of Preventing AIDS Complications (CEPAC)]. Setting and participants Data on test acceptance and costs were from a national randomized trial of HIV testing strategies conducted at 12 substance abuse treatment programs in the United States. Measurements Lifetime costs (2011 US) and quality‐adjusted life years (QALYs) discounted at 3% annually; incremental cost‐effectiveness ratios (ICERs). Findings On‐site rapid HCV testing had an ICER of 18 300/QALY compared with no testing, and was more efficient than (dominated) off‐site HCV testing referral. On‐site rapid HCV and HIV testing had an ICER of 64 500/QALY compared with on‐site rapid HCV testing alone. In one‐ and two‐way sensitivity analyses, the ICER of on‐site rapid HCV and HIV testing remained <100 000/QALY, except when undetected HIV prevalence was <0.1% or when we assumed frequent HIV testing elsewhere. The ICER remained <100 000/QALY in 91% of probabilistic sensitivity analyses. Conclusions On‐site rapid hepatitis C virus and HIV testing in substance abuse treatment programs is cost‐effective at a <100 000/quality‐adjusted life year threshold.